Letter to the Editor Risk of mental illness in doctors – A COVID 19 perspective: Liaquat Medical Research Journal - Khan, Dr. Ahmed Ali (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
There is rising risk of mental illness among doctors in Post- COVID era